RELATIONSHIP BETWEEN PIGMENTS PRODUCTION AND BIOFILM FORMATION FROM LOCAL PSEUDOMONAS AERUGINOSA ISOLATES - & et al., Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current study was designed to explore the association between the pigments production and biofilm construction in local Pseudomonas aeruginosa isolates. Out of 143 patients suffering from burns, urinary tract infections (UTI), respiratory tract infections and cystic fibrosis obtained from previous study by Mahmood (2015), twenty two isolates (15.38%) were identified from (11) hospitals in Iraq, splitted into three provinces, Baghdad, Al-Anbar and Karbala for the duration of June 2017 to April 2018. Characterization was carried out by using microscopical, morphological and biochemical methods which showed that all these isolates belong to P. aeruginosa. Screening of biofilm production isolates was carried out by using nutrient broth supplemented with glucose (0.25%) production medium which encourage this biofilm production. The percentage of pigmented isolates were collected from a total of 143 samples, 2.8% of the isolates from burns, 2.1% isolates from cystic fibrosis and 0.7% isolates from UTI. Quantitative assays for biofilm formation were conducted using ELIZA technique. The results showed that all (22) isolates produced biofilm except one (B1 isolate). Biofilm quantities were varied from strong to medium production in comparison with control (0.0663). Statistical analysis results using Fischer’s Exact test (p<0.05) were non-significant, therefore the pigment production has no association with biofilm formation for all of them.